Repeatability of Magnetic Resonance Elastography‐Derived Mechanical Parameters in Intracranial Meningiomas - Aunan‐Diop, Jan Saip; Friismose, Ancuta Ioana; Halle, Bo; Pedersen, Christian Bonde; Mussmann, Bo; Hojo, Emi; Yin, Ziying; Nortvig, Mathias Just; Lagerstrand, Kerstin; Poulsen, Frantz Rom (Journal of magnetic resonance imaging, 2025)
Magnetic resonance elastography (MRE) quantifies tissue viscoelasticity, offering insights into intracranial meningiomas. MRE-derived parameters, including the storage modulus (G') and the magnitude of the complex modulus (|G*|), may aid neurosurgical planning, but their repeatability remains unexplored in brain tumors. To evaluate the repeatability of G' and |G*| in meningiomas, the influence of tumor volume and spatial location on variability, and ranking stability across paired elastograms. Prospective. Seventeen paired MRE scans from 16 patients with meningiomas (mean age 64 ± 12 years, 10 females) scheduled for resection. MRE was performed on a 3 T system using a single-shot spin-echo echo-planar imaging (SE-EPI) sequence. Tumors were segmented on contrast-enhanced T1-weighted images; distance and volume metrics were extracted. Regions of interest were applied to G' and |G*| elastograms. Repeatability was evaluated using the coefficient of variation (CV%). Ranking stability was assessed by comparing median G' or |G*| values. The difference in CV% was assessed using the Wilcoxon signed rank test. Linear regression assessed the effect of tumor volume and distance from the external occipital protuberance (EOP) on CV%. The Wilcoxon signed-rank test evaluated ranking stability and scan-rescan CV%. Statistical significance was defined as p < 0.05. The difference in CV% G' (14.89 ± 12.32) and CV% |G*| (13.88 ± 12.60) was not significant (p = 0.61). Tumor volume inversely correlated with CV% (G': β = -0.75 |G*|: β = -0.59). Tumor-EOP distance had no significant effect (G': p = 0.58, |G*|: p = 0.23). Rankings remained stable (G': p = 0.82, |G*|: p = 0.71). MRE-derived parameters are repeatable in intracranial meningiomas, with G' and |G*| being equally stable. Larger tumors yielded more consistent estimates. Preserved ranking stability supports the use of MRE in preoperative planning. 2. Stage 2.